Boca de Navios - (:unkn) unknown (Muir, Marshall and Co., Trinidad, 2009)
A picture of the Boca with the view of two islets.
Colour: Black and White; Style: Landscape; Other: Bordered
Keywords: Trinidad and Tobago; Postcards; Ocean--Trinidad and Tobago; Islands--Trinidad and Tobago